Multidimensional real analysis. - Duistermaat, J. J. (Johannes Jisse), 1942-2010 (Cambridge studies in advanced mathematics ;, 2004)
Part two of the authors' comprehensive and innovative work on multidimensional real analysis. Numerous illustrative exercises combined with an exhaustive and transparent treatment of subject matter make the book ideal as either the text for a course, a source of problems for a seminar or for self study.